Does online marketing help in promoting fish? case study on fish companies in Aceh, Indonesia. Issue 1 (February 2021) - Chan, S; Fahlevi, H; Fadli, N; Hasibuan, P; Sofyan, S E; Rianjuanda,; Syukri, M; Saidi, T; Dawood, R
Abstract: This paper aims to analyze the usage of online marketing as a complement to existing offline marketing practices, with the intent to attenuate financial losses in the fishery industry. The current fish marketing business in Aceh still relies heavily on traditional methods, which, with their limited outreach, cause businesses to incur losses in the form of unsold and degrading fish due to longer waiting times between purchases. Unlike other types of commodities, the shelf life of fresh fish is very short. The longer the fish are kept by the fishermen or traders, the more damaged the products will be. However, the availability of consumers willing to buy the fish at any time is uncertain. This problem can be solved if the products are offered to a wider audience by using online marketing. This research uses descriptive qualitative research that produces descriptive data from respondents or observed behavior. Data were collected through interviews and observations in 3 fish export companies in Banda Aceh. The sampling technique used was purposive sampling, based on certain objectives and considerations. The findings suggest that by adding online communication marketing channels to promote fish products, such as Google Ads, as well as joining online marketplace platforms, the risk of suffering losses is reduced.